Autologous Dendritic Cells in Combination With Chemotherapy Restore Responsiveness of T Cells in Breast Cancer Patients: A Single-Arm Phase I/II Trial - Bernal-Estévez, David A.; Ortíz Barbosa, Mauren A.; Ortíz-Montero, Paola; Cifuentes, Claudia; Sánchez, Ramiro; Parra-López, Carlos A. (Frontiers in Immunology, 2021)
Introduction: Animal studies and preclinical studies in cancer patients suggest that the induction of Immunogenic Cell Death (ICD) by neoadjuvant chemotherapy with Doxorubicin and Cyclophosphamide (NAC-AC) recovers the functional performance of the immune system. This could favor immunotherapy schemes such as the administration of antigen-free-autologous dendritic cells (DCs) in combination with NAC-AC to profit as cryptic vaccines immunogenicity of treated tumors. Objective: To explore the safety and immunogenicity of autologous antigen free DCs administered to Breast Cancer Patients (BCP) in combination with NAC-AC. Materials and Methods: A phase I/II cohort clinical trial was performed with 20 BCP treated with NAC-AC (nine who received DCs and 11 who did not (control group)). The occurrence of adverse effects and the functional performance of lymphocytes from BCP before and after four cycles of NAC-AC receiving or not DCs was assessed using flow cytometry and compared with that from Healthy Donor (HD). Flow cytometry analysis using manual and automated algorithms led us to examine functional performance and frequency of different lymphocyte compartments in response to a stimulus in-vitro. This study was registered at clinicaltrials.gov (NCT03450044). Results: No adverse effects grade II or higher were observed associated with the transfer of DCs to patients during NAC-AC. Interestingly, in response to the in-vitro stimulation, deficient phosphorylation of Zap70 and AKT proteins observed before chemotherapy in most patients’ CD4 T cells significantly recovered after NAC-AC only in patients who received DCs. Conclusions: The transfer of autologous DCs in combination with NAC-AC in breast cancer patients is a safe procedure. That in BCP, the administration of DCs in combination with NAC-AC favors the recovery of the functional capacity of T cells suggests that this combination may potentiate the adjuvant effect of ICD induced by NAC-AC on T cells, and hence, potentiate the immunogenicity of tumors as cryptic vaccines.